2021
DOI: 10.2298/abs210909045j
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal feeding habits and ontogenetic diet shift of black bullhead (Ameiurus melas) in Lake Sava (Serbia)

Abstract: The black bullhead is an invasive species that forms dense populations and has a negative impact on the native ichthyofauna. Recent studies indicate that it is one of the most dominant invasive fish species in Serbian waters. Feeding habits based on stomach contents of individuals caught in Lake Sava were analyzed as a first step towards evaluating its possible negative impact on the native fish fauna of the lake. The following indices for diet analysis were applied: vacuity index, frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Black bullhead is a warm‐water species that reaches the highest abundances in artificially created ponds (Copp et al, 2016) and reed beds (Cucherousset et al, 2006b) with dense vegetation (Carpentier et al, 2004). Many studies have confirmed that this species is an opportunistic generalist, foraging on the most abundant and available prey, mainly at night, displaying an ontogenetic diet shift and mainly feeding on fish and fish eggs (Declerck et al, 2002; Leunda et al, 2008; Ruiz‐Navarro et al, 2015; Piria et al, 2017b; Jaćimović et al, 2021). By removing the black bullhead, the pressure it puts on other species by preying on them and competing for food and space will be reduced.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Black bullhead is a warm‐water species that reaches the highest abundances in artificially created ponds (Copp et al, 2016) and reed beds (Cucherousset et al, 2006b) with dense vegetation (Carpentier et al, 2004). Many studies have confirmed that this species is an opportunistic generalist, foraging on the most abundant and available prey, mainly at night, displaying an ontogenetic diet shift and mainly feeding on fish and fish eggs (Declerck et al, 2002; Leunda et al, 2008; Ruiz‐Navarro et al, 2015; Piria et al, 2017b; Jaćimović et al, 2021). By removing the black bullhead, the pressure it puts on other species by preying on them and competing for food and space will be reduced.…”
Section: Discussionmentioning
confidence: 95%
“…Owing to the overlap of their diets, these two limnophilous species can also be considered as competitors, although some research suggests that pumpkinseed has no major competitors in Europe (Fox & Copp, 2014). Studies on the feeding ecology of black bullhead (Leunda et al, 2008; Jaćimović et al, 2021) have shown that this species feeds on pumpkinseed. For this reason, the increase in the number of pumpkinseed may be a consequence of the removal of a larger number of black bullhead individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a relatively high overlap was observed between E. cisalpinus and A. melas . In winter months, the benthivorous A. melas may shift to piscivory, e.g., [ 113 ], while Crustacea may become a significant component of the diet of pikes, in particular for small-sized specimens [ 114 , 115 , 116 ]. Thus, given the relatively small size of E. cisalpinus individuals analyzed in the present study (222–412 mm standard length range; Appendix A , Table A1 ), it can be hypothesized that its diet converged towards that of A. melas , resulting in the observed high overlap.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, those participants with a poorer health status than those diagnosed with ND, QDF, or PW with more complex unbalanced TCMC types tended to use TCM to improve their health. Today, most Hong Kong dwellers accept TCM medications and prefer to choose them for cancer patients to reduce side effects or improve their quality of life [16,17,[34][35][36][37]. We have accounted for and discovered more complex and unbalanced types of TCMC that reflect the poorer health status and usage of Chinese medicines to help treat unbalanced TCMC as alternative medications.…”
Section: Influencing Factors Related To Unbalanced Tcmc Types and The...mentioning
confidence: 99%